A Randomized Controlled Trial of the Efficacy and Respiratory Effects of Patient-controlled Intravenous Remifentanil Analgesia and Patient-controlled Epidural Analgesia in Laboring Women. Issue 1 (March 2015) - Stocki, D.; Matot, I.; Einav, S.; Eventov-Friedman, S.; Ginosar, Y.; Weiniger, C.F.
Abstract : ( Anesth Analg. 2014;118(3):589–597)